SYNTHESIS OF SOME NEW N-SUBSTITUTED-1,2,3,4-TETRAHYDROCARBAZOLE DERIVATIVES AND STUDY THEIR BIOLOGICALACTIVITY - Al-Majidi, Suaad M H; Al-Quaz, Ali M N (Al-Nahrain Journal of Science, 2010)
The aim of this research synthesis compounds different heterocyclic new rings, sulfur and nitrogen containing in structures, substituted-N-(1,2,3,4-tetrahydrocarbazol) [THCz], through the prepared a-chloro-N-tetrahydocarbazol acetamide [2] which was prepared two ways. The firstmethod by condensation [THCz] with chloro acetyl chloride in the presence of triethylamine and dry benzene as solvent. The second method the prepared [THCz]2Hg [1], then condensation withchloroacety chloride in DMSO. Which was treated hydrazinehydrate to give a-hydrazine-Ntetrahydrocabazol acetamide [3]. The hydrazine derivative [3] with five acid anhydrids [Maleic, Phthalic, Succinic, Glutaric and Citraconic] to produce novel diazine which contain the acid refered above on substituted-N-tetrahydrocarbazol acetamide [4a-e] respectively.The compound [2] was treated with each of urea and thiourea to give compounds [5,6] respectively. Followed the cyclization of compounds [5,6] by used p-phenylphencylbromide gave oxazol [7] and thiazol [8] on substituted-N-tetrahydrocarbazol acetamide, furthermore, new Schiffbase [9a-e] were prepared through the reaction of the hydrazine derivative [3] with aromatic aldehydes. The prepared compounds identified by spectral methods [UV, FTIR, H-NMR, 13 CNMR] and measurement some of its physical properties and some specific reaction, furthermore we were studied the effects of the preparing on some strains of bacteria.